The kinetics of ammonium uptake and oxidation across the Southern Ocean - Mdutyana, Mhlangabezi; Sun, Xin; Burger, Jessica; Flynn, Raquel; Smith, Shantelle; Horsten, Natasha; Roychoudhury, Alakendra; Planquette, Hélène; Bucciarelli, Eva; Thomalla, Sandy; Ward, Bess; Fawcett, Sarah (Limnology and Oceanography, 2022)
International audience